Mechanical cues orchestrate monocyte behavior in immune regulation and disease - Yifan Lin; Hardik Makkar; Shuchen Zhang; Bingling Chen; Chaoning Zhan; Kyle Vining (APL Bioengineering, 2025)
Monocytes, key mediators of innate immunity, exhibit remarkable sensitivity to mechanical cues such as extracellular matrix (ECM) stiffness, substrate rigidity, shear stress, compression, and hydrostatic pressure, which shape their activation, differentiation, and functional polarization. Monocytes develop from the bone marrow and populate the vasculature throughout the body. During inflammation, they are recruited to injured or diseased tissues by chemokines and proinflammatory cytokines, modulating local immune responses during embryonic development and adulthood via mechanosensing and mechanotransduction pathways. This review synthesizes recent advances in monocyte mechanobiology. It highlights how the bone marrow ECM mechanics orchestrates myelopoiesis, the role of endothelium and hemodynamic forces in migration, and how tissue mechanics influences monocyte fate in chronic inflammation, fibrosis, and cancer. We discuss the mechanosensitive pathways that govern monocyte behavior in health and disease and therapeutic opportunities that emerge from targeting these mechanisms via biomaterial approaches. Additionally, future directions toward developing mechanotherapy for immune modulation are discussed. By bridging mechanobiology and immunology, this review underscores the potential of mechanical cues as therapeutic targets to reprogram monocyte behavior in disease.